KINERJA INDIVIDUAL KARYAWAN DITINJAU DARI KONSEP THEORY OF PLANNED BEHAVIOR (STUDI KASUS PADA DINAS PERPUSTAKAAN DAN KEARSIPAN KOTA DENPASAR) - Ni Made Rai Juniariani; Putu Dian Pradnyanitasari; Ni Made Intan Priliandani (Behavioral Accounting Journal, 2018)
The purpose of this study is to determine whether the concept of the theory of planned behavior in this research attitude toward behavioral is understood as self-motivation, subjective norms are understood as organizational culture and perceived behavioral control is understood as the ability of work to influence the performance of individual employees. This study uses primary data in the form of answers to questionnaires from employees of the Library and Archives Department of Denpasar City using the survey method. 44 samples were obtained using purposive sampling method. The method of analysis of this study uses multiple linear regression analysis. The results of testing hypotheses show that (1) self motivation positively affects the performance of individual employees. (2) organizational culture positively affects individual employee performance and (3) work ability influences individual employee performance. This research shows that individual employee performance is influenced by factors that exist in themselves and the environment in the organization or company.